Carbon‐Based Flexible Devices for Comprehensive Health Monitoring. Issue 2 (8th January 2023) - Wang, Haomin; Li, Shuo; Lu, Haojie; Zhu, Mengjia; Liang, Huarun; Wu, Xunen; Zhang, Yingying
Abstract: Traditional public health systems suffer from incomprehensive, delayed, and inefficient medical services. Convenient and comprehensive health monitoring has been highly sought after recently. Flexible and wearable devices are attracting wide attention due to their potential applications in wearable human health monitoring and care systems. Using carbon materials with overall superiorities can facilitate the development of wearable and flexible devices with various functions and excellent performance, which can comprehensively and real‐time monitor human health status and prevent diseases. Herein, the latest advances in the rational design and controlled fabrication of carbon materials for applications in health‐related flexible and wearable electronics are reviewed. The fabrication strategies, working mechanism, performance, and applications in health monitoring of carbon‐based flexible devices, including electromechanical sensors, temperature/humidity sensors, chemical sensors, and flexible conductive wires/electrodes, are reviewed. Furthermore, integrating multiple carbon‐based devices into multifunctional wearable systems is discussed. Finally, the existing challenges and future opportunities in this field are also proposed. Abstract : The latest advances in the rational design and controlled fabrication of carbon materials for applications in health‐related wearable electronics are presented here. The fabrication strategies, working mechanism, and performance of electromechanical sensors, temperature/humidity sensors, chemical sensors, and flexible conductive wires/electrodes are reviewed. Their applications and integrating into multifunctional systems are discussed. Finally, the existing challenges and future opportunities are proposed.